Modifikasi Terapi Nebulizer dan Guided Imagery Berpengaruh pada Frekuensi Pernafasan pada Pasien Status Asmatikus - Padila, Padila; Andri, Juli; Sartika, Andry; Andrianto, Muhammad Bagus; Niriyah, Sekani (Journal of Telenursing (JOTING), 2024)
This study aimed to examine the effect of modified nebulizer therapy and guided imagery on respiratory frequency in patients with status asthmaticus. The research design used in this study was quite experimental in one intervention group. The study population was patients with status asthmaticus who were experiencing attacks of status asthmaticus. The population size in this study was 40 respondents. The research sample of 40 people was selected using total sampling. The independent variable in this study was a combination of nebulizer therapy and Guided Imagery, while the dependent variable was a decrease in respiratory frequency in patients with status asthmaticus. The results of the study showed that p-value = 0.02, with 0.02 < 0.05 meaning that there was an effect of the combination of nebulizer therapy and guided imagery on reducing respiratory frequency in patients with asthmatic status in the emergency room at M. Yunus Hospital, Bengkulu City. In conclusion, a combination of nebulizer therapy and guided imagery reduces respiratory frequency in patients with asthmatic status in the emergency room at M. Yunus Hospital, Bengkulu City. Keywords: Respiratory Frequency, Guided Imagery, Nebulizer, Status Asmaticus.